Formulation of the Phasors of Apparent Harmonic Power: Application to Non-Sinusoidal Three-Phase Power Systems - Pedro A. Blasco; Rafael Montoya-Mira; José M. Diez; Rafael Montoya; Miguel J. Reig (Energies, 2018)
In this work, the expression of the phasor of apparent power of harmonic distortion is formulated in the time domain. Applying this phasor along with the phasor of apparent unbalance power allows us to obtain a new set of phasors that include all of the inefficient power components appearing in the transfer of energy in non-linear and unbalanced systems. In this manner, a new model of inefficient power in electrical systems is developed. For each voltage harmonic of order ‘m’ and current harmonic of order ‘n’, a phasor of harmonic apparent power is obtained. Accuracy in the determination of the total apparent power of a system depends on the number of harmonics considered. Each phasor of apparent harmonic power is formed from six mutually orthogonal parameters or components that are calculated from the harmonic voltages at the nodes of the network and the circulating harmonic currents. To demonstrate the validity of the proposed formulation, a four-wire non-linear system formed by two nodes is assessed.